Implementasi PSAK 109 tentang Akuntansi Zakat, Infaq, dan Sedekah (Studi Pada Badan Amil Zakat, Infaq, Sedekah di Kota Mataram) - Nurabiah Nurabiah; Herlina Pusparini; Nur Fitriyah; Yusli Mariadi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2019)
Accountability requires public institutions to make financial reports to describe the organization's financial performance to outsiders. With the issuance of PSAK No. 109 of 2012 concerning zakat, infaq / shadaqah, this standard will give Amil Zakat Institution and Amil Zakat Agency as a reference for reporting zakat, infaq / shadaqah, namely the ability to provide information related to the recognition, measurement and presentation of zakat, infaq / shadaqah. Therefore the purpose of this study is to find out how the implementation of Accounting for Zakat, Infaq and Alms on the Amil Zakat Agency in Mataram City is based on PSAK No.109. The type research used in this study is descriptive research with a quantitative approach. Data used in this study through questionnaires and documentation. The questionnaire was addressed directly to the accounting staff or the head of the finance department and employees of the amil zakat institution in the city of Mataram. Then do the documentation as supporting data from the results of the questionnaire conducted. Data analysis using validity, reliability, and descriptive statistics test. The results of this study conclude that the BAZNAS city of Mataram has fully implemented the use of PSAK No.109 both in terms of recognition, measurement, presentation, and disclosure